An Analytical Approach to Evaluating Nonmonotonic Functions of Fuzzy Numbers - Arthur Seibel; Josef Schlattmann (Advances in Fuzzy Systems)
This paper presents a novel analytical approach to evaluating continuous, nonmonotonic functions of independent fuzzy numbers. The approach is based on a parametric α-cut representation of fuzzy numbers and allows for the inclusion of parameter uncertainties into mathematical models.